(ARTICLE RETRACTED) Social Capital: Trust Building as A Strategy of Developing Madrasa (A Case Study at MI Istiqomah Sambas Purbalingga) - Munjin Munjin (Ijtimā`iyya: Journal of Muslim Society Research, 2018)
This article is RETRACTED, because has been publish before at AL-HAYAT : Journal of Islamic Education on Vol. 1 No. 1, 2017. if you want to read and cite this article, please visit https://alhayat.or.id/index.php/alhayat/article/view/5.